O instituto da antecipação de tutela na proteção dos direitos de propriedade intelectual. - Souza, Marcelo Junqueira Inglez de (2005)
The Brazilian Civil Procedure System underwent significant changes throughout the last decade, which intended to bring the procedural instruments closer to the protected material rights, in response to claims for a more agile and effective legal relief. The institute that allows the anticipation of relief appeared in this context as an alternative to enable such approximation, as it allows immediate satisfaction of the right subject to protection, regardless of a full cognition activity, however, preserving contradictory and legal defense, in order to meet the principle of due process of law. Simultaneously, Brazil is living a moment of growing awareness of the importance of the Intellectual Property Rights and of the necessity of giving due protection to these rights, in order to reach consolidation of its cultural and economic development, while ensuring the integrity of the intellectual production fostering it. Thus, the proposal of this study is to analyze the applicability of the institute that allows the anticipation of relief, as a measure of protection to Intellectual Property Rights, demonstrating its adequacy and effectiveness in injunctions, which aim at preventing wrongful acts against human intellectual creations.